Challenges for contemporary non-profit organizations – theoretical deliberations - Domiter, Małgorzata; Marciszewska, Anna (Management Sciences, 2018)
This article discusses theoretical deliberations about the challenges facing contemporary non-profit organizations and their managements. In these entities, the ability to make wise decisions and the way of putting them into practice are more and more important. This is important above all, due to the constant pressure oriented to the full use of resources and the increase in the effectiveness of the actions taken. A good manager enables an organization to adapt to the changes taking place in an environment despite its simultaneous variability, uncertainty, and complexity. The purpose of the article is to point out the most important challenges facing contemporary nonprofit organizations
Management Sciences, 2018, vol. 23, no. 1, s. 20-26
Keywords: non-profit organizations; management professionalization; non-profit organization management; organizacje non profit; profesjonalizacja zarządzania; zarządzanie organizacjami non profit